Cognitive humanistic therapy Buddhism, Christianity and being fully human - Nelson-Jones, Richard; Sage eBooks (Thousan Oaks, Calif. ; London : SAGE, 2004)
The author describes a new approach to psychotherapy and self-development, based on an understanding of what it means to be 'fully human'. Integrating theory and practice, the book synthesises ideas from the cognitive and humanistic domains of psychotherapy & the religious worlds of Buddhism & Christianity.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Cognitive therapy; Psychotherapy -- Religious aspects -- Buddhism; Psychotherapy -- Religious aspects -- Christianity; Electronic books